Historical trajectories for reclaiming an indigenous identity in mental health interventions for Aotearoa/New Zealand—Māori values, biculturalism, and multiculturalism. (January 2018) - Bennett, Simon T.; Liu, James H.
Abstract: The Treaty of Waitangi (1840), signed between Māori (indigenous people) and the British Crown is today narrated as the foundation of New Zealand's sovereignty. The theory of history and identity is mobilized to (1) articulate how historical narratives such as the story of the encounter between Māori and Pākehā (European New Zealanders) and the signing and subsequent violation of the Treaty between them furnish symbolic resources and possibility spaces that construct, mobilize, and manage ethnic identities; (2) deploy this historical narrative to make sense of the changes to Māori identity in the 20th century and its status and construction today; (3) consider the implications of this historical trajectory in describing mental health situations for Māori people today, including how indigenous values, processes, and constructs might be employed in mainstream, bicultural, and indigenous spaces (from clinical therapy and community-based interventions to social welfare delivery). Indigenous values such as whanaunganga (family relationships), wairua (spirituality), and whakapapa (geneology) are introduced as indigenous concepts in mental health therapy, and linked to recent initiatives by government and iwi (tribes) to improve health and mental health for Māori through different implementation pathways involving more collectivistic structures.